Algorithm postmastectomy breast reconstruction secondary to breast cancer in a reference center in Mexico City - Sánchez-Castrejón, Esperanza; Garza-Arriaga, Daniel; González-Espinosa, Aaron (International Surgery Journal, 2024)
Background: Postmastectomy breast reconstruction represents a challenge for the plastic surgeon. Contemporary techniques offer numerous options, the reconstructive procedure performed depends on the individual profile of each patient, but will also be influenced by the surgeon's preoperative analysis of their individualized risk profile. Methods: Descriptive, longitudinal, and retrospective study. The reconstructed patients with breast cancer sequelae in the period from May 2023 to May 2024 were included. Based on the review of the literature and the experience of our center, a proposal for a breast reconstruction algorithm was formulated to standardize the ideal surgical treatment according to the case. Results: 119 patients were reconstructed using the algorithm to decide the ideal surgical management. Breast reconstruction was performed in 3 stages: the first stage [1st BRS] (119 patients) consisted of a tissue expander, breast implant ± acellular dermal matrix or autologous pedicled flaps after the mastectomy; in the 2nd BRS (68 patients) the expander was replaced with an implant with or without contralateral symmetrization; and finally in the 3rd BRS (18 patients), the reconstruction of the nipple-areola complex ± neurotization, autologous fat transfer and scar remodeling was performed. Conclusions: The algorithm proposed in this paper provides a guide for making decisions about ideal surgical management according to the clinical characteristics of each subgroup of patients to be reconstructed, improving results by making them reliable and predictable, which positively impacts patient's quality of life.